Eksplorasi Gerak Aktif: Mengembangkan Kepercayaan Diri dan Ketangkasan Fisik Anak melalui Fun Agility Game - Abriadi Abriadi; Juhanis Juhanis; Hasmawaty Hasmawaty; Muslim Muslim; Usman Usman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Motor development in early childhood is a crucial foundation for executive functions and psychosocial health. However, the current sedentary lifestyle and gadget dependency hinder the optimization of this physical potential. This community service aims to enhance children's self-confidence and physical agility through the